Motivation of german entrepreneurs to seek equity via crowdfunding: an exploratory study - Roggan, John (2015)
Equity crowdfunding, so financing a project or venture through many small investments of a large group of investors, has received growing attention from the media and scholars. The discussion is about whether crowdfunding could generally transform the way people collect funding for their projects or ventures. Whereas research has so far focused on exploring, why crowdinvestors are motivated to fund ventures, this study focuses on what motivates entrepreneurs to crowdfund. To do so, the study researched the motivation of 11 entrepreneurs to use German equity crowdfunding platforms. Because existing research on the motivation of entrepreneurs stayed largely superficial, this study uses a research approach novel in the field of venture financing, the means-end approach. With this approach the entrepreneurs’ reasoning to use equity crowdfunding was explored holistically, uncovering the entire thought processes leading to the decision to crowdfund. One of the findings is that entrepreneurs use equity crowdfunding to successfully collect funds from rather emotionally investing crowdinvestors to finance their ventures’ future growth and to signal investment viability to follow-up investors. Furthermore, entrepreneurs expect crowdinvestors to be engaged in and help the venture with marketing and feedback. Crowdfunding also allows entrepreneurs to keep decision-making power over the venture better than by using traditional sources of funding. The findings indicate that crowdfunding attracts entrepreneurs who could not secure funding from other sources of capital as well as entrepreneurs who see the additional benefits it can provide over other sources.